Key factors for nature value in Montados - Godinho, Carlos (2014)
Montados are parkland forested areas of anthropogenic origin dominated by cork oak (Quercus suber) and/or holm oak (Q. rotundifolia). They are derived from natural Mediterranean forests, where the use of woodland products (timber, charcoal and cork) is combine with cereal crops and livestock grazing in the understory (Blondel and Aronson 1999). These use resulted in a singular “savanna” like land cover pattern particularly important for the biodiversity associated with farming and forestry systems (Canteiro et al. 2011; Godinho and Rabaça 2011; Simões et al. 2012). As result of the mosaic created by this dynamic heterogeneous landscape which forms a wooded matrix with open areas, scattered woodlands and undisturbed patches of Mediterranean forest and scrublands, montados support a high biological diversity (Díaz et al. 1997, 2003; Blondel and Aronson 1999; Tellería 2001; Tellería et al. 2003; Harrop 2007). According to Tellería (2001) bird richness increases in woodlands southwards along the Iberian gradient, with montados and dehesas showing the higher scores. This pattern is related with the increase presence of edge and open area bird which appears to compensate the lost of forest birds. Due to this diversity of species, birds can have an important role in the valuation of montados as HNV. In the last decades the scientific community has given particular attention to the different roles that birds may play in montados: management options and the breeding bird communities (Camprondon and Brotons 2006; Godinho and Rabaça 2011, Leal at al. 2012; Pereira et al. 2012a; Pulido and Díaz 1992), the influence of cork extraction on birds (Godinho and Rabaça 2011; Leal et al. 2011), relevance of habitat diversity in agroforestry matrices (Leal et al. 2011; Pereira et al. 2012b).